2017
DOI: 10.1093/cid/cix114
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Probiotic, Prebiotic, and Synbiotic Therapies in Reducing Postoperative Complications: A Systematic Review and Network Meta-analysis

Abstract: This network meta-analysis suggests that synbiotic therapy is the first rank to reduce SSI, pneumonia, sepsis, hospital stay, and antibiotic use. Surgeons should consider the use of synbiotics as an adjunctive therapy to prevent POCs among adult surgical patients. Increasing use of synbiotics may help to reduce the use of antibiotics and multidrug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 39 publications
2
50
0
Order By: Relevance
“…Probiotics have been evaluated for preventing nosocomial infection in many smaller studies, and meta-analyses suggest that probiotics are safe and effective at preventing infection in both post-operative and mechanically ventilated patients ( 60 , 61 ). However, the small size of the individual studies, as well as the variable type and dose of probiotic therapy limit strong conclusions.…”
Section: Potential For Modulation Of the Microbiota In The Managementmentioning
confidence: 99%
“…Probiotics have been evaluated for preventing nosocomial infection in many smaller studies, and meta-analyses suggest that probiotics are safe and effective at preventing infection in both post-operative and mechanically ventilated patients ( 60 , 61 ). However, the small size of the individual studies, as well as the variable type and dose of probiotic therapy limit strong conclusions.…”
Section: Potential For Modulation Of the Microbiota In The Managementmentioning
confidence: 99%
“…A meta‐analysis comprising of 2952 patients who underwent either open or laparoscopic procedures showed that administering synbiotics, compared with no therapy, led to a reduction in surgical site infections (relative risk [RR] 0.28; 95%CI, 0.12‐0.64) in adult surgical patients. Those taking synbiotics also developed lower rates of pneumonia (RR 0.28; 95%CI, 0.09‐0.90), sepsis (RR 0.09; 95%CI, 0.01‐0.94) and overall hospital stay (mean = 9.66 days, 95%CI, 7.60‐11.72), but neither synbiotics nor placebo showed overall reduced mortality rates.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…Liu et al in another study (2015) concluded that probiotics reduced postoperative infections in patients with liver metastasis 20 . Three systematic reviews (2017) and one metaanalysis (2015) also confirmed the protective effects of probiotics and synbiotics consumption before ab-dominal surgery, which reduced infective complications such as urinary tract infections, pneumonia and sepsis 15,[20][21][22][23][24] . Liu et al recommended a diet that included bacteria of different strains, and this diet was more useful than single-strain diets for surgical infections and other infections 22 .…”
Section: Discussionmentioning
confidence: 88%